2010
DOI: 10.1523/jneurosci.1017-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Genetic Reversal of Age-Dependent Cognitive Deficits Attributable to Decreased presenilin Function

Abstract: Alzheimer's disease (AD) is the leading cause of cognitive loss and neurodegeneration in the developed world. Although its genetic and environmental causes are not generally known, familial forms of the disease (FAD) are attributable to mutations in a single copy of the Presenilin (PS) and amyloid precursor protein genes. The dominant inheritance pattern of FAD indicates that it may be attributable to gain or change of function mutations. Studies of FAD-linked forms of presenilin ( psn) in model organisms, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 105 publications
3
33
0
Order By: Relevance
“…Importantly, 30-day old PsnB3/+ and PsnC4/+ mutants respond to THIP with an increase in sleep (Figure 5 C , G). Thirty-day old PsnB3/+ and PsnC4/+ flies had impaired LTM consistent with previous reports (Figure 5 D , H) [64]. Thus, 28-day old PsnB3/+ and PsnC4/+ flies were placed onto 0.1mg/mL THIP 2 days prior to and 24 h following training.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, 30-day old PsnB3/+ and PsnC4/+ mutants respond to THIP with an increase in sleep (Figure 5 C , G). Thirty-day old PsnB3/+ and PsnC4/+ flies had impaired LTM consistent with previous reports (Figure 5 D , H) [64]. Thus, 28-day old PsnB3/+ and PsnC4/+ flies were placed onto 0.1mg/mL THIP 2 days prior to and 24 h following training.…”
Section: Resultssupporting
confidence: 88%
“…Mutations in Presenilin have been linked to early onset familial Alzheimer’s disease in humans [63], and previous studies have shown that the age-dependent cognitive deficits associated with mutations in Presenilin can be modeled in Drosophila [64]. As seen in Figure 5 A,E, young Presenilin mutants ( PsnB3/+ , PsnC4/+ ) display normal sleep profiles and exhibit intact LTM as assessed using courtship conditioning (Figure 5 B , F).…”
Section: Resultsmentioning
confidence: 86%
“…1S,3R-ACPD was used in a concentration of 72.2 µM and MPEP at 9.7 µM (Parmentier et al, 1996; McBride et al, 2005, 2010). Both compounds were diluted in H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…There have been certain mutations also studied in Drosophila to evaluate their roles in pharmacological and genetic basis of cognition. 14 …”
Section: Animal Models For Dementiamentioning
confidence: 99%